Aplikasi Pembiayaan Cicilan Emas pada PT Bank Syariah Indonesia Kantor Cabang Pasuruan Sudirman: Indonesia - putri ageng23; Saiful Bakhri (Cashless : Journal of Sharia Finance and Banking, 2024)
The Gold Installment Financing Application implemented by PT Bank Syariah Indonesia Pasuruan Branch Office is a breakthrough in Islamic banking that offers alternative financing for people who want to buy gold in installments using the murabahah principle. This application makes it easy for customers to choose the desired gold product and determine the installment duration according to their financial capabilities. This study aims to evaluate the extent to which this application makes it easier for people to invest in gold and its contribution in encouraging financial inclusion in Indonesia. This study examines the implementation of the gold installment financing program at PT Bank Syariah Indonesia Pasuruan Sudirman Branch Office. Using a qualitative descriptive research method, which aims to describe in depth the implementation process of the gold installment financing application. This approach was chosen to provide a more comprehensive understanding of the various aspects involved in the implementation of the application. This study analyzes how the gold installment program is implemented and its impact in increasing public access to sharia-based investment. The results of the study show that the gold installment program has succeeded in attracting customers from various circles, especially those who are looking for sharia-compliant investments but have limited initial funds. Its implementation is supported by effective marketing strategies and digital platforms, which have improved customer accessibility.